Dynamic planning, conversion, and management strategy of different renewable energy sources: A Sustainable Solution for Severe Energy Crises in Emerging Economies. (11th February 2021) - Chien, FengSheng; Kamran, Hafiz Waqas; Albashar, Gadah; Iqbal, Wasim
Abstract: Green hydrogen energy is a natural substitute for fuel-based energy and it increases a country's long-term energy safety. Pakistan has been a victim of a severe energy crisis for the past few decades. In this context, this research addresses green hydrogen generation and renewable energy supply (i.e., wind, solar, biomass, public waste, geothermal and small hydropower) as an alternate energy source in Pakistan. The assessment is carried out through a two-step framework (i.e., Fuzzy-AHP and non-parametric DEA). Results show that Pakistan has abundant renewable power capacity from wind, which the light-duty transport in the country can opt. Almost 4.89 billion gallons of fuel are consumed annually in Sindh, whereas Punjab uses up around 6.92 billion gallons of fuel annually, which need to be substituted with 1.63 billion kg and 2.31 billion kg of wind-produced hydrogen, respectively. It has been discovered that solar and wind energy attain the same criterion of weights (i.e., 0.070) in-line with the commercial potential criterion. Besides, wind-generated power is ideal for green hydrogen generation in Pakistan, and the subsequent choice for green hydrogen energy is small hydropower and solar, which are also good for green hydrogen generation in the country. Hence, this research offers a solid recommendation for the use of wind energy, which is ideal for the production of Green Hydrogen energy in the country. Highlights: Planning and management strategy of renewable energy sources. Two-step framework Fuzzy-AHP and non-parametric DEA. Sustainable Solution for Severe Energy Crises.